2019
DOI: 10.1111/nep.13627
|View full text |Cite
|
Sign up to set email alerts
|

Effects of early detection of peritoneal catheter migration on clinical outcomes: 15‐years experiences from a single centre

Abstract: Aim Catheter migration is an important cause of catheter malfunction in peritoneal dialysis (PD). The purpose of this study was to investigate the effect of early detection of catheter migration on clinical outcomes. Methods A retrospective review of 135 consecutive patients initiating PD immediately following catheter insertion from 2002 to 2017 was undertaken. In order to detect catheter migration without malfunction early, serial abdominal‐pelvic radiographic examinations were performed according to a prede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…We found that catheter migration was the most common early complication. This finding is similar to the results of a retrospective study by Ko et al 8 who followed 135 patients for 5 years and found that 85.9% of catheter migration occurred in the first 2 weeks after catheter insertion. Crabtree 17 believed that the main reason for catheter migration was that blind penetration might lead to excessive bending of the catheter in the subcutaneous track and incorrect placement of the catheter tip.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found that catheter migration was the most common early complication. This finding is similar to the results of a retrospective study by Ko et al 8 who followed 135 patients for 5 years and found that 85.9% of catheter migration occurred in the first 2 weeks after catheter insertion. Crabtree 17 believed that the main reason for catheter migration was that blind penetration might lead to excessive bending of the catheter in the subcutaneous track and incorrect placement of the catheter tip.…”
Section: Discussionsupporting
confidence: 91%
“…6 Peritonitis and catheter-related complications are the main factors affecting the prognosis of patients on peritoneal dialysis. 7 The incidence of catheter migration can be as high as 48%, 8 and leakage occurs in up to 20% of patients on peritoneal dialysis. 9 To reduce the complications of peritoneal dialysis, previous studies mostly focused on improving the catheterization method.…”
Section: Introductionmentioning
confidence: 99%
“…The catheter survival rates at 5 years mentioned in literature are variable, ranging from 27% to 70.0%. [ 33 34 ] The factor contributing to wide variability of catheter survival between different centers is associated with the experience of centers in PD and number of patients undergoing PD per day. The centers with less than 20 patients on PD had lower technical survival rates in comparison to large centers.…”
Section: Discussionmentioning
confidence: 99%
“…The centers with less than 20 patients on PD had lower technical survival rates in comparison to large centers. [ 16 33 34 ] Our center with 20 years of experience in PD has good numbers of PD patients, which may explain our favorable catheter survival rates. The survival of patients on PD at 5 years mentioned in literature is variable, ranging from 11% to 78%.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the results of Medani et al [ 10 ], in this study, the modified Seldinger technique can significantly reduce catheter-related complications within one month postoperatively, especially the occurrence of catheter migration, compared with open surgery method. It has been reported that the incidence of catheter migration after peritoneal dialysis is 5-35 %, of which 85.9 % occurs in the first two weeks after catheter insertion [ 29 , 30 ]. Our results showed that the incidence of catheter migration in modified Seldinger group was 9.1 %, which was significantly lower than that of the other two groups, but there was no significant difference among the three groups ( P = 0.069).…”
Section: Discussionmentioning
confidence: 99%